Transduodenal surgical papillotomy: Technical aspects in 20 years of experience with contribution to instrumental design - Gil Solares, Orlando; Maglione, Hugo; Melogno, Silvio; Puig, Roberto (Cirugía del Uruguay, 1994)
As opposed to the apparent proscription of the procedure in our country, the authors, without discussing indications, present their instrumental contribution and technical details that in 20 years experience enable them to state that «surgical papillotomy does not increase the morbimortality of simple cholecystectomy» in abssence of the terrible complications and mortality that menace the literature. When discussing results and the bibliographical review, the abundance of the endoscopical procedure is made clear together with the validity of the surgical procedure in the security of the instrumental support and tehcnical perfection.